Coffee classification according to its detachment force: a decision tree-based approach - Meneses, Mariana Dias. [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The world coffee consumption demands high-efficiency crop systems. Consumers appreciate flavor and aroma in this beverage, characteristics that are game-changing in coffee value. A key role to improve this production chain, mechanized harvesting fails in provide coffee fruits selectivity. It means that the industry receives fruits with astringent flavor or fermentation. Because coffee plant has uneven maturation, i.e., green, cherry, and dry fruits, and the harvester settings are generalist, the fruits are detached regardless their maturation stage. The use of Machine Learning techniques improves the traditional agriculture to a digital one, its use in mechanized harvesting enhances selectivity of the coffee fruits. Overall, the present study aimed to classify the coffee fruit detachment force using a Decision Tree Classifier. The experiment was conducted in two field in the Brazilian state of Minas Gerais. A dynamometer was used to measure the detachment force of 23 coffee cultivars. The cultivars were grouped using a cluster algorithm and a Decision Tree classified each group according to the detachment force. The Decision Tree obtained a mean Matthews Correlation Coefficient of 0.81, proving its efficiency in classify the detachment force. Therefore, we proved that Decision Tree can power the mechanized harvesting as a tool to more accurate decision-making settings

O consumo mundial de café exige alta eficiência no sistema da cultura. Consumidores apreciam o sabor e aroma da bebida, características que afetam o valor do café. Peça chave para a cadeia produtiva, a colheita mecanizada falha em promover a seletividade dos frutos. Entregando a indústria, frutos com sabor adstringente ou fermentados. Por causa da maturação irregular na planta do café e dos ajustes generalistas da colhedora, os frutos são derriçados independentemente da sua maturação. O uso de técnicas de Machine Learning melhora a agricultura tradicional para uma agricultura digital, o uso na colheita mecanizada aumenta a seletividade dos frutos colhidos. Visto isso, o presente estudo objetivou classificar a força de desprendimento de frutos do café usando um algoritmo de Árvore de Decisão Classificador. O experimento foi conduzido em duas áreas no estado de Minas Gerais, Brasil. Um dinamômetro foi usado para mensurar a força de desprendimento de 23 cultivares de café. As cultivares foram agrupadas usando um algoritmo de cluster e a Árvore de Decisão classificou cada um dos grupos de acordo com a força de desprendimento. A Árvore de Decisão obteve um coeficiente de correlação Matthews de 0,81, provando a eficiência em classificar a força de desprendimento. Portanto, foi provado que a Árvore de Decisão é uma ferramenta capaz de tornar a tomada de decisão mais acurada, melhorando a colheita mecanizada.
Classificação do café de acordo com sua força de desprendimento: uma abordagem baseada em árvore de decisão
Keywords: Machine Learning; Selective Mechanized Harvesting; Uneven Maturation; Coffee; Agricultura